Complex water-soluble microelements fertilizer effectiveness on grain yields - Dolgopolova Natalia; Eremenko Olga (BIO Web of Conferences, 2024)
Microelement fertilizers (boron, molybdenum, copper, zinc, etc.) play an important role in modern crop production technologies to increase yields and product quality, along with macro fertilizers (nitrogen, phosphorus, potassium). Microelements are needed by plants in very small quantities - their content is one thousandth of a percent of the plant mass. However, each of them has a strictly defined function in metabolism and plant nutrition and cannot be replaced by any other element. Microelements are part of a large number of enzymes. Due to redox processes, enzymes regulate plant respiration, under their influence the chlorophyll content increases, photosynthesis improves, assimilative activity of plants increases. Microelements improve plant metabolism, eliminate functional disorders, activate physiological and biochemical processes. Under the action of microelements, the resistance of plants to fungal and bacterial diseases, to sudden changes in temperature and soil moisture, to winter conditions increases. The supply of microelements to plants is determined by the level of their presence in the soil. The purpose of the research - to determine the effectiveness of different types of application (seed treatment, crop treatment) of the complex water-soluble fertilizer with microelements Novofert on winter wheat crops, in the conditions of grey forest soils of the agricultural complex "Rus", Rylsky district, Kursk oblast.